Analisis terhadap Hadis Dasar Hukum Fatwa DSN No : 12/DSN-MUI/IV/2000 - Munandar Harits Wicaksono (ITB AAS INDONESIA Surakarta, 2021)
Debt has become commonplace to meet the needs of human life. However, because it is only a loan, it must be returned. But sometimes not everyone can do it at the agreed time. Therefore, Islam offers a solution in the form of a hawalah contract. The National Sharia Council then issued a fatwa regarding this matter to strengthen it by mentioning several hadiths as its legal basis. With qualitative methods and literature study, the authors describe the understanding that can be drawn from this hadith. Based on the research results, it was found that there were many differences of opinion in the details of the hawalah contract. Then it was also discovered that one of the hadiths that was used as a reference did not have a degree of shohih and the hadith also did not lead directly to the hawalah contract.